2005
DOI: 10.1186/1471-2296-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for notification of normal laboratory test results: A report from the ASIPS Collaborative

Abstract: BackgroundMany medical errors occur during the laboratory testing process, including lost test results. Patient inquiry concerning results often represents the final safety net for locating lost results. This qualitative study sought to identify, from a patient perspective, specific preferences and factors that influence the process of communicating normal (negative) laboratory test results to patients.MethodsWe conducted 30-minute guided interviews with 20 adult patients. Patients were recruited from two prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 19 publications
2
79
0
Order By: Relevance
“…Studies reporting a preference for US mail or telephone call reflect patients' perceptions that these are the most secure forms of communication. 11 More sensitive test results could therefore affect the degree to which patients are concerned with confidentiality. This study suggests that patients may prefer the option to choose the method of delivery of medical test results, depending on the type of test administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting a preference for US mail or telephone call reflect patients' perceptions that these are the most secure forms of communication. 11 More sensitive test results could therefore affect the degree to which patients are concerned with confidentiality. This study suggests that patients may prefer the option to choose the method of delivery of medical test results, depending on the type of test administered.…”
Section: Discussionmentioning
confidence: 99%
“…9 -11 These studies report a lack of preference in electronic methods of delivering test results, stressing a concern over the security of information with this form of communication. 10,11 However, technology has advanced remarkably, and consumers are more familiar with working with private information over the Internet. This study was conducted to gain greater insight into the general public's preferences to modes of communication between them and their health care provider with regard to specific medical test results.…”
mentioning
confidence: 99%
“…Ignoring the patient safety benefits that might accrue from routinely conveying test results to patients, patients consistently report that they want to know their test results whether normal or abnormal. 17,19 For example, Baldwin and colleagues found that 90 % of patients wanted to be notified of all test results, 16 and a recent trial by Delbanco and colleagues found that providing open access to medical records was well received by patients and providers alike. 27 Several EHR developers have created patient portals, such as Epic's MyChart or the Veterans Health Administration's My HealtheVet, to meliorate communication with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our work built upon prior research that we and others have performed in this area. 10,16,17,19 We collected data on survey respondents' demographic (age, race, sex), educational attainment (categorized as high school or less, some college, completed college, and graduate school or above), and baseline health status (categorized as excellent, very good, good, fair, or poor) information. The full survey instrument is included as Appendix 1.…”
Section: Survey Developmentmentioning
confidence: 99%
See 1 more Smart Citation